Analysing the regional geography of poverty, austerity and inequality in Europe: a human cartographic perspective. Issue 1 (2nd January 2017) - Ballas, Dimitris; Dorling, Danny; Hennig, Benjamin
ABSTRACT: Analysing the regional geography of poverty, austerity and inequality in Europe: a human cartographic perspective. Regional Studies . This paper presents a human cartographic approach to the analysis of the impact of austerity and the economic crisis across Europe's regions. It reflects on past insights and debates on the analysis and mapping of poverty and wealth, and of the effects of austerity in particular. It then presents a wide range of cartograms highlighting social and spatial inequalities across Europe. Finally, the paper highlights the increasingly important role of the field of regional studies in current debates about the future of the European project and of the possibility of a Europe of regions rather than a Europe of nation-states.